2020
DOI: 10.3389/fncel.2020.554405
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Intrinsic and Synaptic Properties of Hippocampal CA1 VIP Interneurons During Aging

Abstract: Learning and memory deficits are hallmarks of the aging brain, with cortical neuronal circuits representing the main target in cognitive deterioration. While GABAergic inhibitory and disinhibitory circuits are critical in supporting cognitive processes, their roles in age-related cognitive decline remain largely unknown. Here, we examined the morphological and physiological properties of the hippocampal CA1 vasoactive intestinal peptide/calretinin-expressing (VIP+/CR+) type 3 interneuron-specific (I-S3) cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 72 publications
1
10
0
Order By: Relevance
“…In the visual cortex, the dendritic arbors of interneurons (in general) were simplified in aged mice ( Eavri et al, 2018 ). However, in other specific interneuronal types, such as the vasoactive intestinal peptide/calretinin-expressing cells in the CA1 region of the hippocampus, no differences were found in dendritic length or number of intersections between young and old mice ( Francavilla et al, 2020 ). However, it has to be noted that we have observed changes in the dendritic spine density only in 9-month females and when grouping both sexes.…”
Section: Discussionmentioning
confidence: 99%
“…In the visual cortex, the dendritic arbors of interneurons (in general) were simplified in aged mice ( Eavri et al, 2018 ). However, in other specific interneuronal types, such as the vasoactive intestinal peptide/calretinin-expressing cells in the CA1 region of the hippocampus, no differences were found in dendritic length or number of intersections between young and old mice ( Francavilla et al, 2020 ). However, it has to be noted that we have observed changes in the dendritic spine density only in 9-month females and when grouping both sexes.…”
Section: Discussionmentioning
confidence: 99%
“…Acute brain slices were prepared from P42-90 mice as previously described (Magnin et al, 2019;Francavilla et al, 2020;Luo et al, 2020). Briefly, animals were deeply anaesthetized with a ketamine-xylazine mixture (ketamine: 100 mg/kg, xylazine: 10 mg/kg) and perfused intracardially with ice-cold sucrose solution (20 mL) containing (in mM): 250 sucrose, 2 KCl, 1.25 NaH 2 PO 4 , 26 NaHCO 3 , 7 MgSO 4 , 0.5 CaCl 2 , and 10 glucose.…”
Section: Patch-clamp Electrophysiologymentioning
confidence: 99%
“…Nevertheless, investigations into the activity profiles and local synaptic communication among CA1 INs of 3xTg-AD mice in vivo have been lacking. Importantly, prior studies on aged mice have identified significant changes in firing properties of type 3 interneuron-specific interneurons (I-S3), which co-express CR and VIP and control the activity of SOM-INs but also of PV-INs in the CA1 hippocampal region (Tyan et al, 2014; Francavilla et al, 2020; Luo et al, 2020). Whether impairments in I-S3 activity might contribute to altered CA1 inhibition and network function in 3xTg-AD mice remains unknown.…”
Section: Introductionmentioning
confidence: 99%